PROGNOSTIGATION OF FINANCIAL CRISIS OF BANK INSTITUTIONS - Martynenko , V.P. (The actual problems of regional economy development, 2016)
The article investigates forecasting the financial crisis banks. Particular focus on developing an integrated measure of financial condition and scale with which to determine the level of financial condition: stable, pre-crisis, crisis, a deep crisis. Using the proposed method of forecasting the crisis banks will allow professionals to settle bankruptcy indicator approaching that acts quantitative characteristic of the financial crisis and is the basis for the current and strategic adjustment of some banking institutions and, consequently, improve the efficiency of crisis management. JEL: G 21